College students’ quality of Life: a study on the effect of forgiveness and self-acceptance - Astuti, Andi Putri Widya; Rahman, Nadya Novia (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
A good quality of life depends on an individual's ability to accept events in their life, which is important for living life effectively. This study examines the effect of forgiveness and self-acceptance on the quality of life of college students using quantitative methods. The subjects were 93 Faculty of Engineering, University of X in Samarinda students selected through probability sampling. Data were collected using a scale of quality of life, forgiveness, and self-acceptance, then analyzed using multiple linear regression. The results of the study showed that: (1) there is a significant effect of forgiveness and self-acceptance on the quality of life, with an F-count value = 77.909 > F-table = 3.10 and a p-value = 0.000, and a contribution of influence (R²) of 63.4%; (2) there is no significant positive effect of forgiveness on the quality of life, with a beta coefficient (β) = 0.089, t-count = 1.190 < t-table = 1.986, and a p-value = 0.237 (p > 0.05); (3) there is a significant influence of self-acceptance on quality of life, with a beta coefficient (β) = 0.746, t-count = 9.953 > t-table = 1.986, and p-value = 0.000 (p < 0.05). This study confirms the importance of forgiveness and self-acceptance in improving students' quality of life.